TINJAUAN YURIDIS TERHADAP SENGKETA KEPEGAWAIAN DALAM PUTUSAN PENGADILAN TATA USAHA NEGARA JAKARTA (Studi Terhadap Putusan Nomor: 237/G/2015/PTUN-JKT) - WIWIK ANGGRAINI, S.H NPM. A2021151099, Jurnal Mahasiswa S2 Hukum Untan (Jurnal NESTOR Magister Hukum, 2017)
ABSTRACT This thesis discusses Juridical Review on Human Resources Dispute in Decision of Jakarta State Administrative Court (Study on Decision Number: 237 / G / 2015 / PTUN-JKT). From the results of this thesis research obtained the basic conclusion In Dispute In Case Number: 237 / G / 2015 / PTUN-JKT. Mangasi Situmeang, S.H., LLM Plaintiff Against the Attorney General of the Republic of Indonesia as Defendant. The Object of Disputes in Case Number: 237 / G / 2015 / PTUN-JKT This Is The Decree of Attorney General of the Republic of Indonesia Number: KEP-IV-551 / C / 08/2015 Date 12 August 2015. Application of Legal Provisions In Case Number : 237 / G / 2015 / PTUN-JKT is the Authority of the State Administrative Court Jakarta In Case Number: 237 / G / 2015 / PTUN-JKT. Based on Article 1 point 9 of the Law of the Republic of Indonesia Number 51 Year 2009 Concerning the Second Amendment to Law of the Republic of Indonesia Number 5 Year 1986 concerning State Administrative Court defines Decision of State Administration is: Decision of State Administration is a written stipulation issued by a state administrative body or officer containing legal action in accordance with applicable, concrete, individual, and final legal rules, which bring legal consequences for a person or a civil legal entity " . And Breaking the Good General Principles of Good Governance, the Issuance of Disputed Objects, brother of Mangasi Situmeang, SH, LLM objected to the actions of the Attorney General of the Republic of Indonesia, which has issued the Attorney General's Decree No. KEP-IV-551 / C / 08/2015 dated August 12, 2015. The acts of the Attorney General of the Republic of Indonesia violate the Good Governance Principles (AAUPB) especially the Principle of Accuracy and Accuracy in issuing a State Administrative Decision. This is as regulated in Article 10 of the Law of the Republic of Indonesia Number 30 Year 2014 About Government Administration. With the Consideration of the Panel of Judges in Deciding the Case Number 237 / G / 2015 / PTUN-JKT stating the Defendants Exception Not Received (niet ont van kelijk verklaard). To grant the claim of the Plaintiff to the whole, to declare that the Decree of the Prosecutor General of the Republic of Indonesia Number: KEPÂ¬IV551 / C / 08/2015 dated August 12, 2015, special serial number 41, on behalf of the Plaintiff, requires the Defendant to revoke the State Administrative Decision In accordance with the Decision Letter of the Attorney General of the Republic of Indonesia No. KEP-IV-551 / C / 08/2015 dated August 12, 2015, special serial number 41, on behalf of the Plaintiff, requires the Defendant to rehabilitate, restore the dignity and status of the Plaintiff as the Chief Prosecutor Country type A in the Provincial Capital, based on applicable laws and regulations. As well as Punishing the Defendant to pay the case fee incurred in this dispute amounting to Rp. 300.000, - (three hundred thousand rupiah). Keywords: Employment Dispute, Decision of State Administrative CourÂ Â Â  Â ABSTRAK Tesis ini membahas tentang Tinjauan Yuridis Terhadap Sengketa Kepegawaian Dalam Putusan Pengadilan Tata Usaha NegaraÂ  Jakarta (Studi Terhadap Putusan Nomor: 237/G/2015/PTUNJKT). Dari hasil penelitian tesis ini diperoleh kesimpulan Dasar Dalam Sengketa Dalam Perkara Nomor :Â Â  237/G/2015/PTUN-JKT. Mangasi Situmeang, S.H.,LLM Penggugat Melawan Jaksa Agung Republik Indonesia Sebagai Tergugat. Adapun ObyekÂ  Sengketa Dalam Perkara Nomor : 237/G/2015/PTUN-JKTÂ  Ini Adalah Surat Keputusan Jaksa Agung Republik Indonesia Nomor: KEP-IV-551/C/08/2015 Tanggal 12 Agustus 2015. Penerapan Ketentuan-Ketentuan Hukum Dalam Perkara Nomor :Â Â  237/G/2015/PTUN-JKT ialah Kewenangan Pengadilan Tata Usaha Negara Jakarta Dalam Perkara Nomor :Â Â  237/G/2015/PTUN-JKT.Â  Berdasarkan Pasal 1 angka 9 Undang-Undang Republik Indonesia Nomor 51Â  TahunÂ  2009 Tentang Perubahan Kedua Atas Undang-Undang Republik Indonesia Nomor 5 Tahun 1986 Tentang Peradilan Tata Usaha Negara mendefenisikan Keputusan tata usaha negara adalah:â€œKeputusan Tata Usaha Negara adalah Suatu penetapan tertulis yang dikeluarkan oleh badan atau pejabat tata usaha negara yang berisi tindakan hukum yang berdasarkan peraturan perundang-undangan yang berlaku, yang bersifat kongkret, individual, dan final, yang membawa akibat hukum bagi seseorang atau badan hukum perdataâ€. Dan Melanggar Asas-Asas Umum Pemerintahan Yang Baik, Penerbitan obyek sengketa, saudara Mangasi Situmeang, S.H.,LLM merasa keberatan atas tindakan Jaksa Agung Republik Indonesia, yang mana telah menerbitkan Surat Keputusan Jaksa Agung Republik Indonesia Nomor: KEP-IV-551/C/08/2015 Tanggal 12 Agustus 2015. Tindakan Jaksa Agung Republik Indonesia, tersebut melanggar Asas-Asas Umum Pemerintahan yang Baik (AAUPB) terutama Asas Ketelitian dan Kecermatan dalam mengeluarkan suatu keputusan Tata Usaha Negara. Hal ini sebagaimana diatur dalam Pasal 10 Undang-Undang Republik Indonesia Nomor 30 Tahun 2014 Tentang Administrasi Pemerintahan. Dengan Pertimbangan Majelis Hakim Dalam Memutuskan Perkara Nomor Nomor: 237/G/2015/PTUN-JKT yang Menyatakan Eksepsi Tergugat Tidak Diterima (niet ont van kelijk verklaard). Mengabulkan gugatan Penggugat untuk seluruhnya, Menyatakan batal Surat Keputusan Jaksa Agung Republik Indonesia Nomor: KEPIV-551/C/08/2015 Tanggal 12 Agustus 2015, khusus nomor urut 41, atas nama Penggugat, Mewajibkan kepada Tergugat untuk mencabut Keputusan Tata Usaha Negara Berupa Surat Keputusan Jaksa Agung Republik Indonesia Nomor: KEP-IV-551/ C/08/2015 Tanggal 12 Agustus 2015, khusus nomor urut 41, atas nama Penggugat, Mewajibkan kepada Tergugat untuk merehabilitasi, mengembalikan harkat, martabat dan kedudukan Penggugat sebagai Kepala Kejaksaan Negeri type A di Ibu Kota Propinsi, berdasarkan peraturan perundang - undangan yang berlaku. Serta Menghukum Tergugat untuk membayar biaya perkara yang timbul dalam sengketa ini sejumlah Rp. 300.000,- (tiga ratus ribu rupiah). Kata Kunci : Sengketa Kepegawaian, Putusan Pengadilan Tata Usaha Negara